Answer:
Option 2nd is correct
![-\frac{1}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D)
Step-by-step explanation:
The nth term for the arithmetic sequence is given by:
![a_n = a+(n-1)d](https://tex.z-dn.net/?f=a_n%20%3D%20a%2B%28n-1%29d)
where,
is the first term
d is the common difference
n is the number of terms.
As per the statement:
From the given graph:
At n =1
![a_1 =4](https://tex.z-dn.net/?f=a_1%20%3D4)
At n =4
![a_4=3](https://tex.z-dn.net/?f=a_4%3D3)
Using the nth term formula for the arithmetic sequence:
![a_4 = a_1+3d](https://tex.z-dn.net/?f=a_4%20%3D%20a_1%2B3d)
Substitute the given values we have;
![3 = 4+3d](https://tex.z-dn.net/?f=3%20%3D%204%2B3d)
Subtract 4 from both sides we have;
![-1 = 3d](https://tex.z-dn.net/?f=-1%20%3D%203d)
Divide both sides by 3 we have;
![-\frac{1}{3} =d](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D%20%3Dd)
or
![d =-\frac{1}{3}](https://tex.z-dn.net/?f=d%20%3D-%5Cfrac%7B1%7D%7B3%7D)
Therefore, the common difference for the given sequence as shown is, ![-\frac{1}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D)